Wound Healing Effects of Edible Bird’s Nests Oinment (Aerodramus fuciphagus) in Alloxan-Induced Male Rats - Dita Ayulia Dwi Sandi; Yaumi Musfirah (Majalah Obat Tradisional, 2019)
Edible bird's nest (Aedrodramus fuchipagus) contains EGF (Epidermal Growth Factor) and sialic acid which is useful in wound healing. The aim of this study was to investigate the effect of edible bird's nest on the injured Alloxan-induced rats to form optimal ointment formulation of edible bird's nest (Aedrodramus fuchipagus) which can heal wounds. The method used in this research is experimental using 25 Sprague Dawley rats divided into 5 groups in which each group consists of 5 rats; Group I was the control group (Vaseline + Betadine®), Group II, III, and IV were the group of EBN + Betadine® with concentrations of 10%, 20%, and 30%; and Group V was of the Sanoskin Meladerm® (SM) + Betadine® group. The rats were modeled for diabetes by inducing Alloxan (150mg/kgBW/i.p) and exposed with DM when the blood sugar level was > 200 mg/dL. The back skins were sliced as long as 2 cm and 2 mm depth and were given treatment according to the group, 1 x daily for 10 days. Parameters that were noticed were length wound, length of the dry wound, and the number of days of scab formation. The results obtained in the control group were 10%, 20%, and 30% on the EBN group, and the SM group on the 9th day were 1.3±0.2449, 0.34±0.427, 0.56±0.4586, 0±0, 0±0. The results of the average length of the dry wound in the control group were 10%, 20%, and 30% on the EBN group, and the SM group were 1±0.5, 2±1.5, 4±0, 8, 1±0.8, and 2±0.63. While the result of the average day of scab formation on the control group was 10%, 20%, and 30% on the EBN groups, SM Groups were 1.3±0.47, 2.2±1.6, 3.8±0.8, 1±0, and 2±0.63. Based on Kruskal Wallis test, there were significant differences in the wound length among treatment groups (sig 0.013) and significant differences in dry wounds among treatment groups (sig 0.046), but there was no difference in the time of scab formation among treatment groups (sig 0.066). In conclusion, edible bird’s nest (Aedrodramus fuchipagus) ointment concentration of 30% is the most optimal ointment to wound healing in Alloxan-induced male rats when compared to Sanoskin Melladerm.